ANALISIS ARUS LALU LINTAS SIMPANG TAK BERSINYAL (Studi Kasus Pada Simpang Jl. Untung Suropati – Jl. Ir. Sutami – Jl. Selamet Riyadi di Kota Samarinda) - Ramadhan, Muhammad Ari (KURVA S JURNAL MAHASISWA, 2014)
The research was conducted at the three arm Unsignalized Intersection (Untung Suropati Street – Ir. Sutami Street and Selamet Riyadi Street). The survey was held on the morning peak hour, off peak hour at noon, and evening peak hour by using manual counter and video camera. The survey held at Untung Suropati intersection on Monday, Thursday and Saturday.The analysis Unsignalized intersection performance used MKJI 1997. The analysis of critical Lag used Raff method. The analysis of traffic potential capacity of right turn from minor street on intersection traffic conflict volume used HCM 1994, 2000 formula.Within the result of the both intersection performance, it could be acknowledged that the degree saturation is more than 1,00 and the average delay is more than 15 second/pcu and queue probability is more than 35%. These indicate that both intersection condition are bad. The critical lag value of Untung Suropati intersection is 2.81 second. Thus, the behaviors of drivers within crowded traffic do not wait gap. The traffic potential capacity of right turn of minor street traffic within traffic conflict volume of Untung Suropati intersection on the east approach 0,03% - 0,37%. The right turn vehicle absorption of the minor street in Untung Suropati intersection is very small so that there is a vehicle heaping in minor street. Within Timoho intersection, the turn right vehicle absorption of the narrow minor street is small happened on the east approach of minor street.Untung Suropati intersection performance is not feasible as unsignalized intersection, based on the graph setting intersection that intersection handling should be implemented at the intersection in question is the intersection priorities setting (the roundabout) and untenable as unsignalized intersections.